Hypovitaminosis D and anthropometric measurement association in young healthy females of Karachi - Sheikh, Mareeha; Iqbal , Nazish (International Journal of Endorsing Health Science Research, 2018)
Background: Vitamin D deficiency recognized as a pandemic problem around the globe. In the last few decades, the incidence of hypovitaminosis D is affected severely in both genders of Pakistan. Due to economical hurdles and sociocultural practices, the prevalence of hypovitaminosis D is much higher in females which leads to age-related chronic bone & skeletal deformities. To find out vitamin D profile associated with anthropometric measurement of young healthy Pakistani females. Methodology: 115 healthy female participants were recruited for the study. Demographic profile, physical activity status, dietary habits and anthropometric measurements of participants were collected by means of a questionnaire designed for the study. Participantsto two groups, vitamin D deficient (VDD) group, and vitamin D adequate (VDA) group. Anthropometric measurements of both groups included body mass index (BMI), waist-hip ratio (WHR), mid-upper arm circumference (MAC), triceps skinfold (TSF), corrected mid-upper arm muscle area (CMUAMA) and circumference of thigh size, neck size, biceps size and wrist size. Data were analyzed using Microsoft office 2013. A t-test was applied to find out the associations. P value < 0.05 was considered significant. Results: P-value for all anthropometric measurements, was found to be non-significant. Unhealthy dietary habits were much higher in VDD group as compared to VDA group. Thus, it was found that there is a high prevalence of hypovitaminosis D in young Pakistani females. Conclusion: Hypovitaminosis has great influence on physical activity, anthropometric measurement and dietary intake of an individual.